(3MSf GdJhSd Edi UfGYI GdJQSds - (3GdTgGH eMehO , eMehO Hf SdeGf Hf agO Hf eMehO GdMfHdj GdMdHjGdOeTbj, CHhGdSfGA,J (B725 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg LGYd GdEfSGf eNHhAG JMJ GddSGf aEfg deG LYd Gddg dj aj cJGHI GdEfTGA QRbG HGTQJ HSHHg ef hXGFagG eG HGTQJ, hYGTQJ ef CLdg ef CcGHQ CgdgG hCFeJgG ef YGTQJ hQCjJ ef ePGgHge s
(3BNQgG (B:s
(3haj gPG ebfY hCfG CSCd Gddg GdJLGhR Yf Rdd GddSGf hCQZH Edi eJCedg aj GdEZVGA Yf YKQI Gdbde hcHhI GdNGWQ hShAI GdPgf ade jcf EdG GdJeKjd aj Jdc GdCfhGY hPdc jMUd HGdcdGe GdebHhd Ohf GdeNJGQ s
(3GfXQ GdLRA GdChd HQbe (B193 (3COHs
(3fSNI ofbdJ ef fSNI YdjgG NW CHj MjGf GdCfOdSj HELGRI GdeDda dg hYdi GdfSNI YOI JedcGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B167s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B258 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B666s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs